2010
DOI: 10.1007/s00394-010-0134-7
|View full text |Cite
|
Sign up to set email alerts
|

Protection against increased intestinal permeability and bacterial translocation induced by intestinal obstruction in mice treated with viable and heat-killed Saccharomyces boulardii

Abstract: Oral treatment with viable or heat-killed cells of S. boulardii maintained intestinal integrity and modulated the immune system in a murine IO model, preventing bacterial translocation and intestinal lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 46 publications
1
31
0
1
Order By: Relevance
“…The probiotic yeast S. boulardii increases the expression of ZO-1 in T84 cells (186) and has been associated with decreased intestinal permeability in numerous studies (155,(187)(188)(189)(190). Similarly, both Bifidobacterium longum and LGG have been shown to induce the upregulation of claudin-1, ZO-1, and occludin protein levels in keratinocytes (185).…”
Section: Other Mechanisms Of Action Of Beneficial Microbes and Probiomentioning
confidence: 99%
See 1 more Smart Citation
“…The probiotic yeast S. boulardii increases the expression of ZO-1 in T84 cells (186) and has been associated with decreased intestinal permeability in numerous studies (155,(187)(188)(189)(190). Similarly, both Bifidobacterium longum and LGG have been shown to induce the upregulation of claudin-1, ZO-1, and occludin protein levels in keratinocytes (185).…”
Section: Other Mechanisms Of Action Of Beneficial Microbes and Probiomentioning
confidence: 99%
“…Several studies have shown that the administration of probiotic organisms can increase total secretory IgA levels in rodents (148,(152)(153)(154), which may contribute to the control of C. difficile bacteria (72,(77)(78)(79)(80)(81). S. boulardii, for example, increases total secretory IgA levels in conventional rats and mice as well as in germfree mice colonized with S. boulardii (148,(152)(153)(154)(155). Studies of Bifidobacterium animalis subsp.…”
Section: Other Mechanisms Of Action Of Beneficial Microbes and Probiomentioning
confidence: 99%
“…The exact mechanisms by which S. boulardii mediates these protective effects are not fully understood. However, administration of S. boulardii in animal models has been shown to increase secretory IgA, interleukin 10 (IL-10), and IL-10 induced T regulatory cells [5], [6] as well as to preserve intestinal epithelial integrity in colitis models [7][9] and to degrade specific pathogen toxins [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of immune response A) By acting as an immune stimulant S. boulardii effects on innate immunity 1) Triggers activation of complement and migration of monocytes and granulocytes [Caetano et al 1986] 2) Enhances the number of Küpffer cells in germfree mice [Rodrigues et al 2000] S. boulardii effects on adaptive immunity 1) Enhances the mucosal immune response and secretory IgA intestinal levels [Buts et al 1990;Czerucka et al 2007;Generoso et al 2011;Szajewska et al 2007;Zanello et al 2009] 2) Enhances systemic immune response and levels of serum IgG to C. difficile toxins A and B.…”
Section: Action Of Saccharomyces Boulardii Referencesmentioning
confidence: 99%
“…[ Generoso et al 2011] 3) Interferes with NF-κB-mediated signal transduction pathways, in immune and colonic epithelial cells [Buts, 2009;Dahan et al 2003;Mumy et al 2008;Pant et al 2007;Sougioultzis et al 2006] 4) Blocks activation of ERK1/2 and MAP kinases Kyne et al 2001;Mumy et al 2008;Sougioultzis et al 2006] 5) Decreases NO and inhibits production of inducible NOS ] 6) Modulates T cell migratory behavior and increases trapping of T helper cells into mesenteric lymph nodes [Dalmasso et al 2006a;Fidan et al 2009;Sougioultzis et al 2006;Thomas et al 2009] 7) Stimulates production of anti-inflammatory molecules in human colonocytes such as PPAR-γ Lee et al 2005Lee et al , 2009Mumy et al 2008] ERK, extracellular signal-regulated kinase; IL, interleukin; INF-γ, interferon gamma; IgA, Immunoglobulin A; IGF, insulin growth factor; MAP, mitogen-activated protein; NF-κB, nuclear factor kappa B; NO, nitric oxide; NOS, nitric oxide synthase; PPAR-γ, peroxisome proliferator-activated receptor-gamma; TNFα: tumor necrosis factor alpha product to product variation, and stability, number of strains used in the probiotic preparation and dose of the probiotic used.…”
Section: Action Of Saccharomyces Boulardii Referencesmentioning
confidence: 99%